The moderating effect of motivations on the relationship between obtaining ISO 9001 certification and organizational performance. Issue 5 (10th August 2015) - Valmohammadi, Changiz; Kalantari, Mohsen
Abstract : Purpose: – The purpose of this paper is threefold, first to investigate if ISO 9001 certified companies in an Iranian province (Kermanshah) perform better than non-certified ISO 9001. Second, what is the main motivation of the manufacturing companies of Kermanshah province on obtaining ISO 9001 certification, i.e., internal or external motivations. And finally, if ISO 9001 certified companies with high scores of internal motivations, show better levels of performance in comparison with certified companies obtaining low scores of internal motivations. Design/methodology/approach: – A survey questionnaire was distributed to the 350 companies with ISO 9000 certification, and a total of 287 usable responses were returned. Using a structural equation model, this study empirically examines the relationship between ISO 9000 implementation and firm performance, and the moderating role of firm motivation on organizational performance. Findings: – The results demonstrate that ISO 9001 certified companies show better organizational performance than non-certified ISO 9001 companies and internal motivations play more important role on obtaining ISO 9001 certificate than external motivations. Also ISO 9001 certified companies with high scores of internal motivations show better levels of performance than those ISO 9001 certified companies with low scores of internal motivations. Research limitations/implications: – The sample is restricted to only a single region and manufacturing, so it would be strongly recommended that data be gathered from various parts of Iran including both manufacturing and service industries. As in this study the data gathered were cross-sectional, it is recommended in order to gain deeper understanding of the cause-and-effect relationship among the variables data to be gathered longitudinally. Originality/value: – This study represents a first attempt to construct a conceptual framework that integrates the motivations behind implementing ISO 9000 certification, and ISO 9000 performance in the context of Iran and gives a particular focus on the Iran manufacturing companies.